Und was steht denn vor der Tür? : Salon. - Lux, Harm (Zürich : Shedhalle, 1990)
Ach, Xerxes ; Bühlmann, Max ; Gränicher, thomas ; Mattioli, Enrico ; Schiess, Lisa ; Thomet, Irene ; Weilenmann, Harry J. ; Zatti, René ; Zimmermann, Daniel ; etc.
Und was steht denn vor der Tür?, Shedhalle, Zürich, 2. December 1990 - 13. Januar 1991
Duits
kunstcatalogus